Decomposing socio-economic inequality in colorectal cancer screening uptake in England. (June 2015) - Solmi, Francesca; Von Wagner, Christian; Kobayashi, Lindsay C.; Raine, Rosalind; Wardle, Jane; Morris, Stephen
Abstract: Colorectal cancer (CRC) is the second largest cause of cancer death in the UK. Since 2010, CRC screening based on Faecal Occult Blood testing has been offered by the NHS in England biennially to all persons age 60–69 years. Several studies have demonstrated a gradient in uptake using area-level markers of socio-economic status (SES), but few have examined the individual-level contributors to the gradient. We aimed to quantify the extent of SES inequality in CRC screening uptake in England using individual-level data, and to identify individual factors associated with this inequality. We used data from 1833 participants (aged 61–69) in Wave 5 (collected in years 2010/11) of the English Longitudinal Study of Ageing (ELSA) eligible for having been sent at least one CRC screening invitation. Uptake was defined by self-report of ever having been screened as part of the National Screening Programme. We assessed socio-economic inequality using the corrected concentration index of uptake against SES rank, which was derived by regressing a range of SES markers against net non-pension household wealth. Other demographic and health-related variables were included in the analysis. Factors associated with inequality were measured using concentration index decomposition. There was a significant pro-rich gradient in screening uptake (concentration index: 0.16, 95% CI:0.11–0.22), mostly explained within our model by differences in non-pension wealth (38.7%), partner screening status (15.9%), sickness/disability (13.5%), and health literacy (8.5%). Interventions aimed at reducing inequalities in CRC screening uptake should focus on improving acceptability of screening in populations with low levels of education and literacy barriers. Highlights: We found a significant SES gradient in the uptake of CRC screening in ELSA. Education and health literacy made large contributions to inequalities in screening uptake. Participants who were sick or disabled had lower probability to screen and were affected by a high degree of inequality. Having a partner who screened was strongly associated with screening uptake. Interventions to reduce inequalities in uptake should aim to improve screening acceptability in groups with poor health literacy.